Association Between Patients Behavior, Housing Conditions and Malaria Severity in the Fourteen Military Hospital, Margibi County, Liberia - Gabriel Zean; Heny Arwati; Linda Dewanti; Atika; Moses Tende Stephens (Universitas Airlangga, 2025)
Introduction: Malaria has been a significant public health issue in Liberia, with behavioural and environmental factors influencing transmission and consequences. This study evaluated the association between patient behavior and housing condition with malaria status and severity in a military hospital in Margibi County, Liberia, in 2024. Methods: A cross-sectional study utilising 54 patients infected with P. Falciparum, where 53.7% were male, aged 20 to 49, and 46.3% were female, examining the association between patients' behaviour, housing condition and malaria severity in the Fourteenth Military Hospital in 2024. The association between variables was analysed using Chi-square and Fisher's exact tests. Results and Discussion: The association between patient behavior and housing conditions with malaria case status was statistically insignificant, as was the association between these factors and malaria severity. Small sample sizes and unmeasured confounders may not have provided sufficient statistical power to detect significant differences between groups, even though stronger associations between certain variables might exist but were undetected due to limited data. Further research with a more controlled design and larger sample sizes will be necessary to investigate the association between these variables further. Conclusion: There was no significant association between patient behavior and housing conditions with malaria case status or severity. A more systematic approach to data collection, incorporating factors related to malaria status and severity, could provide a clearer understanding of the contributors to P. falciparum infection status and disease, which can be correlated with patient behavior.